Decoding the Plot of “The Ice Palace” (1920) by F. Scott Fitzgerald - Ida Ayu Gede Laksemi Dewi; I Nyoman Udayana; I Made Rajeg (Loquēla (Journal of Linguistics, Literature, and Education), 2024)
F. Scott Fitzgerald's "The Ice Palace" remains a seminal work of American literature, delving into themes of identity, cultural displacement, and the search for belonging. This study aims to dissect and analyze the intricate plot structure of "The Ice Palace," employing a qualitative method to uncover deeper insights into Fitzgerald's storytelling techniques and thematic undercurrents. Drawing five essential components of plot, the research scrutinizes each narrative element, tracing the protagonist's journey from exposition to resolution. Utilizing content analysis of the story, the study reveals how Sally Carrol Happer's experience in the Northern environment, particularly her harrowing ordeal in the ice palace, leads to a profound realization of her true self. The resolution, marked by Sally Carrol's decision to return to the South, highlights the thematic emphasis on embracing one's identity and finding fulfillment in authenticity. Through close examination of plot dynamics, this research offers fresh perspectives on Fitzgerald's narrative craftsmanship and thematic resonance in "The Ice Palace."